Study of changes in wholesale and retail prices of citrus crops in Latakia Governorate during the period (2014-2022). - ياسمين غندور ,; غسان يعقوب,; غسان بدور , (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to identify changes in citrus crop prices in Latakia governorate during the period (2014-2022), and to measure the absolute and relative marketing margin, and marketing shares. To achieve the previous objectives, the study relied on secondary data issued by the ministry of agriculture and Agrarian reform in Syria during the period studied and issued form the directorate of internal trade and consumer protection in Latakia governorate for the same period, where the research relied on the descriptive analytical approach with the aim of describing the marketing routes for the citrus crop. Presenting , organizing and analyzing data using descriptive methods and mathematical equations, and the method of price spread to calculate marketing margins between the Different marketing stages and measure the marketing shares of the product, the wholesaler, and the retailer from the consumer ,s lira, and the use of indices of production prices and costs to measure average changes in production costs, and product prices, wholesale and retail. The results of the research showed that the costs of citrus production increased by 1481% during the period studied, and this was accompanied by an increase in prices at Approximately the same rate, which led to the product not obtaining the appropriate profit. The relative marketing margin between the various marketing channels, product and wholesale, in the year 2014 reached 34.5%, increasing then in 2022 to about 35.7% as for the relative marketing margin in the wholesale and retail sector, it decreased from 21.7% in 2014 to 17.6% in 2022. Likewise, for the producer and retail sector, it decreased from 48.5% to 47.1% it is also noted that the relative marketing margin for this sector in creased compared to the previous two paths. As for the distribution of the marketing shares of the producer, the Wholesaler, and the retailer from the consumer lira according to the same order 29.4%, 17.6% the results also showed a decrease in the average marketing efficiency for the period studied, reaching about 46.4% as a result of the significant increase in marketing costs.